PENERAPAN MODEL KOMUNIKASI PEMASARAN AISAS DAN TEORI KOMUNIKASI HAROLD D. LASWELL PADA BOBOBOX BERSAMA DANIEL MANANTA - Fajriani, Mediva Dyah; Nursholih, Sonson (Telkom University, 2023)
Along with the development of technology and communication, Bobobox, a brand that operates in the field of accommodation (hotels) in the city of Bandung, offers a form of marketing to show a value quite different from other brands of its kind. Bobobox uses social media, especially Instagram, to introduce its products or services to the general public. This study aims to find out how Bobobox applies the AISAS marketing communication model and the Harold D. Communication Theory of Lasswell through digital media. This writing uses qualitative methods that are descriptive through the analysis of case studies on how Bobobox conveys its brand value. The results of this research show that Bobobox uses digital marketing communication strategies through various variable content that visually builds interpretations for the audience about the value of Bobobox by collaborating with Daniel Mananta as an influencer that brings relatable topics to its market segmentation. Keywords: AISAS, communication model, digital media, value